Longevity Leadership: Strategi SDM Mengelola Pemimpin Senior dan Tantangan Silver Economy dalam Suksesi Kepemimpinan - Siti Rahmadani; Yoga Prastiyo; Rania Shabira Aryani; Mochammad Isa Anshori (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
The global rise in life expectancy toward the 100-year threshold has accelerated the emergence of the silver economy, significantly affecting organizational leadership structures, particularly in terms of succession stagnation risks and potential loss of institutional knowledge. This study aims to develop a comprehensive longevity leadership strategy to manage senior leaders and optimize leadership succession in the context of demographic transition. The research employs an integrative literature review with thematic analysis of reputable international and national journal articles published within the last five years. The findings reveal that effective longevity leadership strategies emphasize repositioning senior leaders from operational roles to strategic mentors through knowledge-sharing mechanisms and phased retirement approaches. Furthermore, successful succession in an aging workforce depends on role flexibility and the establishment of new psychological contracts that recognize and value the wisdom of senior leaders. This study contributes theoretically by proposing a dynamic succession model that bridges intergenerational gaps. Practically, it offers guidance for human resource practitioners in designing age-inclusive retention strategies and leadership transition policies.Overall, the proposed strategy supports organizational stability while fostering sustainable innovation through the optimal utilization of senior human capital.